Child Maltreatment: Neglect of Child Welfare After Sexual Violence - Syahrul Akmal Latif; Riky Novarizal (Global Writing Academica Researching and Publishing, 2023)
The treatment of children receives after experiencing sexual abuse incidents often results in acts of child maltreatment from the family, community, and school. This child maltreatment indicates that there has been a neglect of the well-being of children after experiencing sexual abuse incidents. This study aims to explain and analyze cases, treatment, and conditions in a group of girls after experiencing sexual abuse incidents. Because so far there are only a few studies that pay special attention to the condition of children after experiencing sexual abuse incidents. This study is descriptive qualitative. Data collection was carried out through the process of reading online news using the search keyword